2005
DOI: 10.1007/s00259-005-1853-5
|View full text |Cite
|
Sign up to set email alerts
|

Further investigations of morpholino pretargeting in mice—establishing quantitative relations in tumor

Abstract: Contrary to conclusions arrived at in our earlier study, the results of this study show that tumor CEA sites were not saturated even at the highest antibody dose investigated, that accessibility of MORF sites in tumor by (99m)Tc-cMORF was unhindered and that the maximum percent tumor accumulation of (99m)Tc-cMORF depended only on the tumor delivery efficiency of (99m)Tc-cMORF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 13 publications
4
66
0
Order By: Relevance
“…The MORF-MN14 was synthesized using a commercial Hydralink™ method (Solulink Biosciences, San Diego, CA) [15]. The average gpm of MORF-MN14 used in this study was 1.00 ± 0.03 compared to an average gpm of only 0.17 to 0.30 when an earlier method of conjugation was used [9,10]. A new lot of MN14 antibody was used to investigate the influence the dosage of MORF-MN14.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The MORF-MN14 was synthesized using a commercial Hydralink™ method (Solulink Biosciences, San Diego, CA) [15]. The average gpm of MORF-MN14 used in this study was 1.00 ± 0.03 compared to an average gpm of only 0.17 to 0.30 when an earlier method of conjugation was used [9,10]. A new lot of MN14 antibody was used to investigate the influence the dosage of MORF-MN14.…”
Section: Methodsmentioning
confidence: 99%
“…Pretargeting interval-Earlier experience indicated that a pretargeting interval of 2 d was reasonable [10].…”
Section: Timingmentioning
confidence: 99%
See 3 more Smart Citations